Familial Gordon syndrome associated with a PIEZO2 mutation. Issue 1 (7th October 2016) - Alisch, Franz; Weichert, Alexander; Kalache, Karim; Paradiso, Viola; Longardt, Ann Carolin; Dame, Christof; Hoffmann, Katrin; Horn, Denise
Abstract : Gordon syndrome or distal arthrogryposis type 3 is a rare autosomal dominant disorder characterized by contractures of upper and lower limbs. It is distinguishable from other forms of distal arthrogryposis by cleft palate and short stature. Recently, Gordon syndrome has been associated to heterozygous mutations in the piezo‐type mechanosensitive ion channel component 2 gene (PIEZO2). Different mutations of this gene also cause distal arthrogryposis type 5 and Marden–Walker syndrome. Dysfunction of this ion channel provides pleiotropic effects on joints, ocular muscles, and bone development. Here, we present a family with three affected individuals exhibiting multiple contractures (metacarpo‐phalangeal and interphalangeal joints as well as elbow, shoulder, knee, and ankle joints), clubfeet, short stature, bifid uvula/cleft palate, and a distinct facial phenotype including ptosis. In addition, mild intellectual disability and delay in psychomotor development are obvious. The multigenerational phenotypic spectrum of Gordon syndrome is present in the 37‐year‐old father, his 4‐year‐old son and a male neonate showing typical signs of arthrogryposis in the prenatal ultrasound examination already seen at 13 week of gestation. In all affected family members, we identified the PIEZO2 mutation c.8057G>A (p.Arg2686His) by Sanger sequencing. Our analysis indicated that mild delay in psychomotor development and intellectual disability could be part of the phenotypic spectrum of Gordon syndrome. © 2016 Wiley Periodicals, Inc.